Efficiency evaluation of vibration milling of mineral materials in the context of solid wastes from hydrogen fluoride production; European Journal of Natural history; № 6 - Fedorchuk Yu. M. Yuri Mitrofanovich; Daneker V. A. Valery Arkadjevich; Volkov A. A.; Adam A. M.; Anikanova L. A. (Ecological technologies, 2015)
Title screen